The unintended consequences of maternity leaves: How agency interventions mitigate the negative effects of longer legislated maternity leaves - Hideg, Ivona; Krstic, Anja; Trau, Raymond N C; Zarina, Tanya (Journal of applied psychology, 2018)
To support women in the workplace, longer legislated maternity leaves have been encouraged in Scandinavian countries and recently in Canada. Yet, past research shows that longer legislated maternity leaves (i.e., 1 year and longer) may unintentionally harm women's career progress. To address this issue, we first sought to identify one potential mechanism underlying negative effects of longer legislated maternity leaves: others' lower perceptions of women's agency. Second, we utilize this knowledge to test interventions that boost others' perceptions of women's agency and thus mitigate negative effects of longer legislated maternity leaves. We test our hypotheses in three studies in the context of Canadian maternity leave policies. Specifically, in Study 1, we found that others' lower perceptions of women's agency mediated the negative effects of a longer legislated maternity leave, that is, 1 year (vs. shorter, i.e., 1 month maternity leave) on job commitment. In Study 2, we found that providing information about a woman's agency mitigates the unintended negative effects of a longer legislated maternity leave on job commitment and hireability. In Study 3, we showed that use of a corporate program that enables women to stay in touch with the workplace while on maternity leave (compared to conditions in which no such program was offered; a program was offered but not used by the applicant; and the program was offered, but there was no information about its usage by the applicant) enhances agency perceptions and perceptions of job commitment and hireability. Implications for theory and practice are discussed. (PsycINFO Database Record (c) 2018 APA, all rights reserved).